2020
DOI: 10.3390/nu12020522
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Peptide Concentrations and Peptide-Reactive Immunoglobulins in Patients with Eating Disorders at Inclusion in the French EDILS Cohort (Eating Disorders Inventory and Longitudinal Survey)

Abstract: Eating disorders (EDs) are increasingly frequent. Their pathophysiology involves disturbance of peptide signaling and the microbiota–gut–brain axis. This study analyzed peptides and corresponding immunoglobulin (Ig) concentrations in groups of ED. In 120 patients with restrictive (R), bulimic (B), and compulsive (C) ED, the plasma concentrations of leptin, glucagon-like peptide-1 (GLP-1), peptide YY (PYY), and insulin were analyzed by Milliplex and those of acyl ghrelin (AG), des-acyl ghrelin (DAG), and α-mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Previous studies suggested that aMSH-reactive Immunoglobulins were modified in patients with AN [32,33]. Our findings are in accordance with recent studies [24,25] showing that aMSH-reactive immunoglobulins are not modified in patients with AN compared with controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies suggested that aMSH-reactive Immunoglobulins were modified in patients with AN [32,33]. Our findings are in accordance with recent studies [24,25] showing that aMSH-reactive immunoglobulins are not modified in patients with AN compared with controls.…”
Section: Discussionsupporting
confidence: 92%
“…Affinity kinetics of plasma extracted IgG for acyl-ghrelin, desacyl-ghrelin, leptin and aMSH were analyzed by surface plasmon resonance (SPR) on a BIAcore T200 (GE Healthcare) according to previously published protocol [24]. Briefly, peptides were diluted in 10 mM sodium acetate buffer (pH 5.0) and coated on the CM5 sensor chip (GE Healthcare).…”
Section: Appetite-regulating Peptides-reactive Immunoglobulin G Affinitymentioning
confidence: 99%
“…High plasma levels and changes of affinity kinetics of autoantibodies reacting with a-MSH and ACTH seem to be caused by the exposure to stress as a result of concomitant hypothalamic-pituitary-adrenal (HPA) axis activation (110,111). These results support the hypothesis that changes in affinity of autoantibodies reacting with a-MSH and ACTH are involved in the pathogenesis of AN and BN and that increased levels of high-affinity anti-a-MSH or anti-ClpB (a-MSH conformational mimetic produced by Enterobacteriaceae) autoantibodies can induce bulimia, while increased levels of low-affinity anti-a-MSH autoantibodies can induce anorexia (24,110,112) (Table 1).…”
Section: The Ghrelin Leptin and Melanocortin System In An And Bnsupporting
confidence: 69%
“…We reversed the anticoagulant tube back and forth 10-12 times so that the blood and anticoagulant could mix well. And the blood samples were centrifuged immediately at 2000 g for 10 min at room temperature for the collection of plasma [15], which were stored at − 80°C until further analysis.…”
Section: Sample Collectionmentioning
confidence: 99%